The Glaser collection - Austrian Centre for Digital Humanities and Cultural Heritage (2015)
A go!digital project conducted by BASIS-OEAW in cooperation with ACDH-OEAW to digitize squeezes and various materials from the Academies Glaser archive collection. The collection of the Austrian scholar and explorer Eduard Glaser (1855-1908) was acquired in 1910 by the Academy of Sciences in Vienna. The epigrapher and specialist in the South-Arabian language brought back a huge amount of medieval Arabic manuscripts, and stone inscriptions, nowadays spread over Europe, as well as squeezes of the non-transportable ones, photographs, glass-negatives, diaries, and notes of historical importance.